(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article gives the dimensions of a ’beehive house’ that was excavated near Arbroath in 1860, as well as the finds that were unearthed on the site. Several graves were discovered near the site, although the author refuses to speculate about who might have been buried there. He also discusses some of the area’s local folklore and toponymy.